Genetic variation of yellow pigment and its components in foxtail millet (Setaria italica (L.) P. Beauv.) from different eco-regions in China - Yan-bing YANG; Guan-qing JIA; Li-gang DENG; Ling QIN; Er-ying CHEN; Xin-jun CONG; Ren-feng ZOU; Hai-lian WANG; Hua-wen ZHANG; Bin LIU; Yan-an GUAN; Xian-min DIAO; et al. (Journal of Integrative Agriculture, 2017)
Kernel color is an important trait for assessing the commercial and nutritional quality of foxtail millet. Yellow pigment content (YPC) and carotenoid components (lutein and zeaxanthin) of 270 foxtail millet accessions, including 50 landraces and 220 improved cultivars, from four different eco-regions in China were surveyed using spectrophotometry and high performance liquid chromatography methods. Results indicated that YPC had rich variance, ranging from 1.91 to 28.54 mg kg−1, with an average value of 17.80 mg kg−1. The average YPC of improved cultivars (18.31 mg kg−1) was significantly higher than that of landraces (15.51 mg kg−1). The YPC in cultivars from the Loess Plateau spring sowing region (LPSSR) was the highest (20.59 mg kg−1), followed by the North China summer sowing region (NCSSR, 18.25 mg kg−1), the northeast spring sowing region (NSSR, 17.25 mg kg−1), and the Inner Mongolia Plateau spring sowing region (IMPSSR, 13.92 mg kg−1). The variation coefficients of YPC in cultivars from NSSR, LPSSR, and IMPSSR were higher than that from NCSSR. A similar carotenoid profile was also obtained for 270 foxtail millet cultivars. Lutein and zeaxanthin accounted for approximately 55–65% of YPC in accessions. The lutein content was higher than zeaxanthin content in all cultivars. The ratio of lutein to zeaxanthin ranged from 1.51 to 6.06 with an average of 3.34. YPC was positively correlated with lutein (r=0.935, P<0.01), zeaxanthin (r=0.808, P<0.01), and growth duration (r=0.488, P<0.01), whereas it was negatively correlated with grain protein (r=–0.332, P<0.01) and 1 000-kernel weight (r=–0.153, P<0.05). Our study is useful for screening and selecting cultivars with high levels of yellow pigment and for enhancing phytochemical concentrations in breeding programs.